Progress in the Mechanism of Autophagy and Traditional Chinese Medicine Herb Involved in Dementia - Pengyu Tao; Jing Ji; Simeng Gu; Qian Wang; Yuzhen Xu (Frontiers Media S.A., 2022)
Dementias is a kind of neurodegenerative disease, which occurs among the aging population. Current therapeutic outcome for dementia is limited. The medical use of herbal plant has a rich history in traditional Chinese medicine practice for thousands of years. Herbal medicine (HM) may provide a positive effect for prevention and treatment in dementia. As an alternative treatment to dementia, there has been a growing interest in HM extracts in scientific community as a result of its promising study results, mainly in animal experiment. At the molecular level, HM extracts trigger autophagy and reduce generation of reactive oxygen species (ROS) while inhibiting inflammation and reduce neurotoxicity. Experiments both in vivo and in vitro have identified certain potential of HM extracts and natural products as an important regulator factor in mediating autophagy, which might contribute to the improvement of dementia. This brief review not only summarizes the mechanism of autophagy in dementia but also offers a general understanding of the therapeutic mechanism of HM extracts in treating dementia and evaluates the potential clinical practice of HM in general.